Szego polynomials: some relations to L-orthogonal and orthogonal polynomials - Bracciali, Cleonice Fátima [UNESP]; da Silva, A. P.; Ranga, A. S. (Elsevier B.V., 2003)
We consider the real Szego polynomials and obtain some relations to certain self inversive orthogonal L-polynomials defined on the unit circle and corresponding symmetric orthogonal polynomials on real intervals. We also consider the polynomials obtained when the coefficients in the recurrence relations satisfied by the self inversive orthogonal L-polynomials are rotated. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: Szego polynomials; chain sequences; Three term recurrence relations